TANGGUNG JAWAB LEMBAGA PEMASYARAKATAN MAGELANG TERHADAP TAHANAN TITIPAN - Putra Aji Widya P.; M. Endriyo Susila; Yeni Widowaty (Legal Standing : Jurnal Ilmu Hukum, 2021)
This study aims to examine the responsibility of an institution, namely the correctional institution in the city of Magelang in reviewing detainees in custody or those who are temporarily or during the completion of the sentencing process. The method used in this research is sociological normative legal research. The author uses the type of legal research above in a simple way, but the type of normative legal research is more prominently displayed with the aim of better understanding the regulations that apply in the juridical study of the responsibilities of the Correctional Institution towards prisoners entrusted in Magelang. From the results of the study, it was concluded that the juridical responsibility for prisoners entrusted to be in the Correctional Institution is the party or agency that entrusted them according to the level of examination. Physical responsibility for prisoners entrusted to be in the Correctional Institution is the party entrusted by the detaining party, namely the Detention Center but the Correctional Institution can also function as a Detention Center.